IDEAL MAKSIMAL DAN IDEAL PRIMA NEAR-RING - Saman Abdurrahman (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2010)
This study discusses the near-ring ideal covering the ideal near-ring ideal and ideal prime near-ring. Next, we studied the relationship between ideal near-ring ideal and ideal prime near-ring.